The Subject Supposed to LOL: Slavoj Žižek and the Event of the Internet - Clint Burnham (tripleC: Communication, Capitalism & Critique)
Is the Internet an Event? Does it constitute, as Žižek argues an Event should, a reframing of our experience, a retroactive re-ordering of everything we thought we knew about the social but were afraid to ask Facebook? In this contribution, Clint Burnham engages with Žižek’s recent work (Less than Nothing, Event, Absolute Recoil) as a way to argue, first, that in order to understand the Internet, we need Žižek’s “immaterial materialism,” and, in turn, to understand Žižek’s thought and how it circulates today, we need to think through digital culture and social media.   As regards the Internet, then, no cynical disavowal, no Facebook cleanses, no shutting off the wifi: les non-dupes errent, or those who distance themselves from social media and the like are the most deceived. Next: the Internet’s two bodies: digital culture is both the material world of servers, clouds, stacks and devices and the virtual or affective world of liking, networking, and the mirror stage of the selfie. And here we must confront the “obscene underside” of digital culture: not only the trolls, 4chan porn, and gamergate bro’s, but also the old fashioned exploitation of labour, be it iPhone assembly-line workers at Foxconn, super-exploited “blood coltan” miners in the Congo, “like farmers” in India, or social media scrubbers in the Phillipines, who ensure your feeds are “clean” of porn, beheadings, and other #NSFW matter. These last concerns, then, mean we also have to think about what Žižek calls the “undoing of the Event” of the Internet, the betrayal of the Internet, its diseventalization.